The incidence of venous thromboembolism in total joint replacement during COVID-19 pandemic: Has lockdown had an innfluence?. (December 2020) - Khan, S. A.; Logan, P.; Asokan, A.; Handford, C.; Rajgor, H. D.; Khadabadi, N. A.; Moores, T.; Targett, J.
No abstract available